Treating a GAD65 Antibody-Associated Limbic Encephalitis with Basiliximab: A Case Study - Widman, Guido; Golombeck, Kristin; Hautzel, Hubertus; Gross, Catharina C.; Quesada, Carlos M.; Witt, Juri-Alexander; Rota-Kops, Elena; Ermert, Johannes; Greschus, Susanne; Surges, Rainer; Helmstaedter, Christoph; Wiendl, Heinz; et al. (Frontiers in Neurology, 2015)
Background Antibodies (ABs) against the 65-kDa isoform of the intracellular enzyme glutamate decarboxylase (GAD65) have been found in limbic encephalitis (LE) and other neurological conditions. The direct significance of anti-GAD65-ABs for epilepsy is unclear. However, in histological preparations from biopsies of resective epilepsy surgeries, predominantly cytotoxic T-lymphocytes were detected making close contacts to neurons. Activated T-lymphocytes can, in turn, be selectively controlled by therapeutic interleukin-2 receptor Abs, such as basiliximab. Case presentation We report of a 25-year-old male patient with epilepsy since the age of 18 and displaying clinical signs of LE and a high titer of GAD65 ABs in cerebrospinal fluid (CSF) and serum. Monthly, repetitive, intravenous cortisone pulse therapies that were initially administered for 6 months failed to improve his condition. Subsequent flow-cytometry analysis of CSF showed especially an increased fraction of activated HLA-DR+ CD8+ T-lymphocytes (fCD8+TL) when compared to controls. Thus, a second, intravenous cortisone pulse therapy with an additional basiliximab dose of 20 mg/month was started. After 3 months, the fCD8+TL in the CSF normalized; after 6 months, the psychological impulse-control deficits normalized; and after 11 months the patient was seizure free. However, 7 weeks later, seizures and, later on, psychological deficits recurred and fCD8+TL was once again present in the CSF. Flumazenil PET, magnetic resonance imaging-volumetry, and neuropsychological changes during therapy are described. Conclusion The correlation of the fCD8+TL in the CSF with clinical and paraclinical measures of disease activity combined with the unambiguous response to basiliximab strongly argues in favor of the putative pathogenic role fCD8+TL in anti-GAD65 LE. The clinical relapse at the end of the observation period might be due to the formation of human anti-drug ABs, a well-known complication of therapy with chimeric ABs.